2013
DOI: 10.1007/s00277-013-1879-x
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine combined with rituximab for patients with relapsed or refractory diffuse large B cell lymphoma

Abstract: Patients with relapsed or refractory diffuse large B cell lymphoma (DLBCL) are treated with salvage regimens and may be considered for high-dose chemotherapy and autologous stem cell transplantation if disease is chemosensitive. Bendamustine is active in indolent B cell lymphomas and chronic lymphocytic leukemia but has not been extensively studied in aggressive lymphomas. This trial examines the combination of bendamustine and rituximab in patients with relapsed and refractory DLBCL. Patients received bendamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 32 publications
1
84
1
1
Order By: Relevance
“…One limitation of that study, similar to limitations in our study, is that responses were not analyzed by cell of origin. 32 Assessing responses to brentuximab vedotin by cell of origin of DLBCL would be an interesting exploratory analysis, although CD30 expression does not clearly correspond to the GCB or the ABC subtype of DLBCL. [15][16][17][18] Other limitations of this study are the lack of a comparator arm, absence of central review of response, and lack of analysis of response by other potentially important prognostic markers, such as Bcl-2 or c-Myc.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of that study, similar to limitations in our study, is that responses were not analyzed by cell of origin. 32 Assessing responses to brentuximab vedotin by cell of origin of DLBCL would be an interesting exploratory analysis, although CD30 expression does not clearly correspond to the GCB or the ABC subtype of DLBCL. [15][16][17][18] Other limitations of this study are the lack of a comparator arm, absence of central review of response, and lack of analysis of response by other potentially important prognostic markers, such as Bcl-2 or c-Myc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trials evaluating the use of bendamustine in diffuse large B‐cell lymphoma, an intermediate grade lymphoma, are under way. The result of a phase II clinical trial to evaluate the effectiveness of bendamustine in previously treated diffuse large B‐cell lymphoma reported that the overall response rate was 62.7%, the complete response rate was 37.3%, and the progression‐free survival was 6.7 months 17. Bendamustine is expected to become a key drug for the treatment of intermediate grade lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previously-reported treatments for elderly patients with relapsed aggressive B-cell lymphomas ineligible for autologous transplantation included the rituximab-gemcitabine-oxaliplatin protocol with a 5-year PFS and OS rate of 14% [10], the rituximab-bendamustine protocol, which resulted in a median PFS time of 4 months in 1 study [11] and of 8 months in another [12], and the R-DHAP protocol, which was associated with a median OS of 28 months in a study that also included other entities [13]. With the R-ICE protocol, the 3-year PFS and OS rates were 32 and 35%, respectively, and the median PFS and OS times were 9 and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 99%